Adab Paradigm in Legal Education (Case In Indonesia) - Rokan, mustapa Khamal; permata, cahaya (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Law violations committed by law enforcers cannot be separated from the paradigm and legal teaching system applied by law faculties that produce law graduates. This paper discusses the adab paradigm in law teaching in law faculties in Indonesia. The method used in this paper is qualitative by describing the data obtained through interviews, observations, and readings of the existing literature. The study results indicate that the teaching of law in Indonesia is positivistic. The education of law is more about teaching the law that applies in a country that is contained in the legislation and its derivatives. This can be seen from the structure of the course and the content of the course syllabus where there are only six (6) courses that are directly related to etiquette. The factors that influence the shift in valuesin the teaching of law include educators and the learning system. While the model of inculcating values for law students can be done by inculcating character at the beginning of the lecture, exploring and elaborating on philosophy and legal principles in each course, incorporating ethical valuesin each course, drawing grades through cases (Project Base), inculcating values through ideal legal figures, creating separate courses related to etiquette, and incorporating customary valuesinto courses. Of the seven models above, incorporating ethical values in each course is the most ideal model to be applied